The influence of gender on CD4+ Treg cell function in acute ischemic stroke prognosis - Na, Hui; Gu, Yue; Liu, Yang; Xia, Shiliang (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to evaluate the influence of gender on the prognostic value of CD4+ Treg cells in patients with acute ischemic stroke.MethodsA prospective cohort study was conducted at Minhang Hospital, enrolling 225 patients with acute ischemic stroke. CD4+ Treg cell counts were measured by flow cytometry within 24 h of admission, and stroke prognosis was assessed at 3 months using the mRS. Univariate and multivariable logistic regression models were used to identify prognostic factors, and an interaction analysis was conducted to examine whether gender moderated the effect of Treg cell levels on outcomes.ResultsMultivariable analysis revealed that infarct volume (OR = 1.08, 95% CI: 1.03–1.13, p = 0.0028), NIHSS score (OR = 1.30, 95% CI: 1.17–1.45, p < 0.0001), and WBC count (OR = 1.32, 95%CI: 1.05–1.67, p = 0.0172) were independent predictors of stroke prognosis. Higher CD4+ Treg cell counts were significantly associated with better prognosis in male patients (OR = 0.995, 95% CI: 0.992–0.999, p = 0.008), but showed no significant association in female patients (OR = 0.999, 95%CI: 0.998–1.001, p = 0.826). The interaction analysis confirmed that gender significantly moderated the relationship between CD4+ Treg cell counts and stroke prognosis (p = 0.0198). Additionally, segmented regression analysis revealed a nonlinear association between Treg cell counts and stroke prognosis in male patients, with specific thresholds indicating variable effects on prognosis.ConclusionGender plays a critical role in modulating the immunoregulatory effects of CD4+ Treg cells on stroke prognosis, with male patients deriving significant benefit from higher Treg cell counts.